TERAPI KOGNITIF DALAM RESOLUSI KONFLIK UTUSAN LINTAS BUDAYA - Meidy Widiastuti Sangkianti (Sekolah Tinggi Alkitab Tiranus, 2019)
On the one hand, cross cultural workers within cross cultural ministry are rich in potential, but on the other hand they are vulnerable to communication problems. The issue of conflict resolution among cross cultural workers is one of the most common things occurs and cannot be ignored. The hermeneutical approach to the Epistle to Philemon combined with cognitive therapy suggest decent and practical foundations in assisting conflict resolution among cross cultural workers.